2021
DOI: 10.3389/fncel.2021.647109
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Characterization of Immortalized Mouse Cortical Astrocytes From Wildtype and Connexin43 Knockout Mice

Abstract: We transduced mouse cortical astrocytes cultured from four litters of embryonic wildtype (WT) and connexin43 (Cx43) null mouse pups with lentiviral vector encoding hTERT and measured expression of astrocyte-specific markers up to passage 10 (p10). The immortalized cell lines thus generated (designated IWCA and IKOCA, respectively) expressed biomarkers consistent with those of neonatal astrocytes, including Cx43 from wildtype but not from Cx43-null mice, lack of Cx30, and presence of Cx26. AQP4, the water chann… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…The high capability of endothelial cells to dynamically modulate their Cxs expression profile and the permeability of the channels they are forming is significant. Indeed, even if no direct contact between astrocytes and endothelial cells occurs in the NVU, these cells can interact in an in vitro coculture system [ 57 , 118 , 119 , 120 ]. The capability of endothelial and glial cells to effect such plastic changes, shaped the idea that they are able to modulate intercellular communication, ion homeostasis, and paracrine mediators release in a context dependent manner [ 113 , 114 , 115 ].…”
Section: Connexins Signatures Of Nvu Componentsmentioning
confidence: 99%
“…The high capability of endothelial cells to dynamically modulate their Cxs expression profile and the permeability of the channels they are forming is significant. Indeed, even if no direct contact between astrocytes and endothelial cells occurs in the NVU, these cells can interact in an in vitro coculture system [ 57 , 118 , 119 , 120 ]. The capability of endothelial and glial cells to effect such plastic changes, shaped the idea that they are able to modulate intercellular communication, ion homeostasis, and paracrine mediators release in a context dependent manner [ 113 , 114 , 115 ].…”
Section: Connexins Signatures Of Nvu Componentsmentioning
confidence: 99%
“…At 14 days, flasks were shaken at 180 rpm for 12-24 h in an incubated shaker (Ecotron HT) to remove residual tissue and microglia. 43 , 44 Astrocytes were cultured up to passage 3 for use in experiments.…”
Section: Methodsmentioning
confidence: 99%
“…To study astrocyte/endothelial cell interactions, the mouse brain endothelioma cell line bEND.3 was used (American Type Culture Collection #CRL‐2299, RRID: CVCL_0170). We previously showed that this cell line mimics the effects of primary brain endothelia on GLT1 expression (Lee et al, 2017), and this cell line has been used to study the mechanisms that control tight junction formation (Cibelli et al, 2021; Pu et al, 2022; Sasson et al, 2021; Stamatovic et al, 2009). In addition, this cell line has the advantage of being a homogeneous population of cells.…”
Section: Methodsmentioning
confidence: 99%